Taking context and strategy seriously: the contracting out decision in the U.S. public education. Issue 9 (2nd September 2021) - Rho, Eunju; Kim, Soojin; Han, Sumin
ABSTRACT: This study examines how contracting decisions can be influenced by organizational contexts, managerial strategies, and the interaction between the environment and strategies, building on Miles and Snow's strategy typology—prospectors, defenders, and reactors. Our empirical evidence shows that the fragmented political context affects contracting decisions and only the reactor strategy leads to less contracting. Moreover, the impact of top-level managers' particular strategic stances on contracting decisions becomes greater as fiscal power is centralized within a relatively simpler intergovernmental political setting. Likewise, a higher level of financial deficiency can ameliorate the negative effect of a defender strategy on contracting decisions.